Antimicrobial susceptibilities of clinical isolates of Acinetobacter baumannii from Singapore. - Kuah, B G (1994)
The in vitro activities of 17 antimicrobial agents alone or in combination against 70 clinical isolates of Acinetobacter baumannii from Singapore were determined by broth microdilution. The MICs of amoxicillin, ampicillin, ceftazidime, ceftriaxone, gentamicin, and piperacillin for 90% of the strains were > or = 128 micrograms/ml. Addition of sulbactam to ampicillin produced improved activity, whereas adding tazobactam to piperacillin did not. The MICs of amikacin, ciprofloxacin, and imipenem for 90% of the strains were 32, 32, and 16 micrograms/ml, respectively.